Repeated occurrences of methanogenic zones, diagenetic dolomite formation and linked silicate alteration in southern Bering Sea sediments (Bowers Ridge, IODP Exp. 323 Site U1341). (March 2016) - Wehrmann, L.M.; Ockert, C.; Mix, A.C.; Gussone, N.; Teichert, B.M.A.; Meister, P.
Abstract: Diagenetic precipitates, such as dolomite, and the chemistry of residual deeply buried porewater often represent the only traces of past biogeochemical activity in marine sediments. A 600 m thick sedimentary section, recently drilled at Integrated Ocean Drilling Program (IODP) Site U1341 on Bowers Ridge (southern Bering Sea), provides insight into such a 4.3 Ma old paleo-diagenetic archive. Hard-lithified calcite–dolomite layers, and laminae of disseminated carbonate, were recovered in diatom-rich sediments over a depth range of 400 m. Carbon isotope values of the diagenetic carbonates between −16.6 and −14.4‰ (VPDB) and strontium isotope ratios of dolomites close to past seawater values suggest carbonate precipitation induced by the production of dissolved inorganic carbon (DIC) during elevated rates of organic carbon mineralization, primarily via sulfate reduction, at shallow sediment depth below the paleo-seafloor. Diagenetic carbonates at 280–440 m below seafloor were likely also produced by the intermittent onset of sulfate reduction coupled to the anaerobic oxidation of methane (AOM) at sulfate–methane transition zones (SMTZ). These microbially mediated processes do not occur in the sediment at this site at present but were likely connected to the presence of a methanogenic zone at 2.58–2.51 Ma. A minimum in sulfate concentrations in modern porewaters and low sedimentary Ba/Al ratios resulting from former sulfate depletion are reminiscent of the presence of this large methanogenic zone. The minimum in sulfate concentrations is reflected in a minimum in magnesium concentrations, less radiogenic strontium and isotopically light calcium in the porewater. It is proposed that magnesium was removed from the porewater during carbonate precipitation and volcanic ash alteration which occurred in the former methanogenic zone and also released strontium with a less radiogenic isotope ratio and isotopically light calcium into the porewater. The isotopic composition of porewater calcium was also influenced by ammonium–calcium exchange on clay minerals and carbonate recrystallization. Our study elucidates the response of porewater element concentrations and isotopic profiles interlinked with the formation of diagenetic carbonates to changes in the deposition of organic carbon in sediments of deeper water sites (>2000 m water depth) over prolonged timescales. It shows that variations in biogeochemical processes in response to changes in oceanographic conditions and a dynamic subseafloor biogeochemical zonation have to also be taken into account at these deep water sites for a global assessment of organic carbon burial fluxes and remineralization.